Korean want to share their knowledge - Abd Razak, Dzulkifli (2008)
The occasion was to commemorate the withdrawal 60 years ago of Soviet forces from North Korea, the Democratic People's Republic of Korea, which declared Pyongyang as its capital. The keyword that underlines North Korea for the last six decades is best described as "selfreliance" or juche. During its first fiveyear plan which began in 1957, it was reported that industrial productivity was 3.5 times more than the earlier target. By 1970, it declared itself an industrialised country based on socialism. In the 1980s, however, the economic situation deteriorated and in the 1990s, there was largescale starvation,. Many died, forcing reclusive North Korea to seek international aid.